2006
DOI: 10.1002/humu.9440
|View full text |Cite
|
Sign up to set email alerts
|

V(D)J recombinase mediated inter-chromosomalHPRT alterations at cryptic recombination signal sequences in peripheral human T cells

Abstract: The V(D)J recombinase enzyme complex is responsible for the development of a diverse immune system by catalyzing intra-molecular rearrangements of immunoglobulin (Ig) and T cell receptor (TCR) genes at specific recombination signal sequences (RSSs). This enzyme complex has also been implicated in mediating pathologic and non-pathologic intra-and inter-molecular genomic rearrangements at cryptic (Ψ) RSSs outside the immune system loci in lymphoid cells. We describe here two V(D)J recombinase mediated genomic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…HPRT1 has frequently been shown to carry a complex deletion/insertion rearrangement, where gross regions of the TCRA locus are inserted into the HPRT1 locus. 28,30,96 One of the three TCRA insertions identified in this study (the BP site of 2 other cases could not be identified) showed involvement of a cRSS at the HPRT1 locus (Table 3). A BICD insertion (9q22) into HPRT1 locus has also been described.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…HPRT1 has frequently been shown to carry a complex deletion/insertion rearrangement, where gross regions of the TCRA locus are inserted into the HPRT1 locus. 28,30,96 One of the three TCRA insertions identified in this study (the BP site of 2 other cases could not be identified) showed involvement of a cRSS at the HPRT1 locus (Table 3). A BICD insertion (9q22) into HPRT1 locus has also been described.…”
mentioning
confidence: 76%
“…5 Non TCRassociated chromosomal aberrations such as deletional aberrations (SIL-TAL1) and insertions (HPRT1) have also been appointed as V(D)J recombination-mediated events based on the presence of cRSSs at BP sites. [28][29][30][31] Until now, TCR-associated translocation mechanisms have mainly been evaluated for only a few BP sites by means of ex vivo experiments, 4,6,31,32 basically confirming the concept of RAG mistargeting to cRSSs. These oncogenes and their respective BP sites were usually chosen for their high frequency in T-ALL and also because of the probability that they would function as a cRSS based on structural criteria.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Intermolecular recombinations possess a characteristic signal junction, where one of the signal ends of the integrating fragment is precisely fused to a genomic RS. The other RS is fused to DNA immediately flanking the genomic RS (pseudo-hybrid junction) [19, 21, 24, 25] (Figure 2b, Table 1). As characterized in detail by the Nadel group [21], such events are probably mediated by intermolecular recombination (or recombination in trans ): a V(D)J recombination between the extrachromosomal RS in the signal end fragment and the genomic RS.…”
Section: How Often?mentioning
confidence: 99%